Curcumin alleviates 1-methyl- 4-phenyl- 1,2,3,6-tetrahydropyridine- induced Parkinson’s disease in mice via modulating gut microbiota and short-chain fatty acids - Cai, Benchi; Zhong, Lifan; Wang, Qitong; Xu, Wendi; Li, Xi; Chen, Tao (Frontiers in Pharmacology, 2023)
Background: The microbiota–gut–brain axis has been proposed as a potential therapeutic target of PD. The effects of curcumin against Parkinson’s disease have been demonstrated; however, its neuroprotective mechanisms remain unknown. Our study investigated the potential mechanisms through which curcumin ameliorates Parkinson’s disease via the microbiota–gut–brain axis. Methods: Mice were randomly divided into four groups: control, Curcumin, MPTP, and MPTP + Curcumin. Motor deficits and gastrointestinal dysfunction were assessed using behavioral test, intestinal motility test, and fecal parameter measurement. The loss of dopaminergic neurons and intestinal barrier function was measured using Western blot and immunofluorescence. Shotgun metagenomic sequencing and LC-MS were parallelly performed on mice feces to investigate alterations in microbiota and metabolites. Results: Curcumin alleviated motor deficits and the loss of dopaminergic neurons in MPTP-induced mice. Curcumin ameliorated gastrointestinal and intestinal barrier dysfunctions in MPTP-induced mice. Curcumin reduced gut microbial dysbiosis and modulated carbohydrate metabolism in MPTP-induced mice. Curcumin restored short-chain fatty acid (SCFA) profiles in MPTP-induced mice. Conclusion: Concurrently, these results indicate that curcumin inhibits Parkinson’s disease by regulating the gut microbiota and short-chain fatty acids.